Understanding the impact and causes of 'failure to attend' on continuity of care for patients with chronic conditions - Byrne A-L; Baldwin A; Harvey C; Brown J; Willis E; Hegney D; Ferguson B; Judd J; Kynaston D; Forrest R; Heritage B; Heard D; et al. (PLOS, 2021)
AIM: To understand the impact and causes of 'Failure to Attend' (FTA) labelling, of patients with chronic conditions. BACKGROUND: Nurse navigators are registered nurses employed by public hospitals in Queensland, Australia, to coordinate the care of patients with multiple chronic conditions, who frequently miss hospital appointments. The role of the nurse navigator is to improve care management of these patients. Evidence for this is measured through improvement in patient self-management of their conditions, a reduction in preventable hospital admissions and compliance with attendance at outpatient clinics. Failure to attend (FTA) is one measure of hospital utilisation, identifying outpatient appointments that are cancelled or not attended. METHOD: The cohort for this study was patients with multiple chronic conditions, and nurse navigators coordinating their care. Data describing the concept of FTA were thematically analysed twelve months into this three year evaluation. RESULTS: Although the patient is blamed for failing to attend appointments, the reasons appear to be a mixture of systems error/miscommunication between the patient and the health services or social reasons impacting on patient's capacity to attend. Themes emerging from the data were: access barriers; failure to recognise personal stigma of FTA; and bridging the gap. CONCLUSION: The nurse navigators demonstrate their pivotal role in engaging with outpatient services to reduce FTAs whilst helping patients to become confident in dealing with multiple appointments. There are many reasons why a patient is unable to attend a scheduled appointment. The phrase 'Failure to Attend' has distinctly negative connotations and can lead to a sense of blame and shame for those with complex chronic needs. We propose the use of the neutral phrase "appointment did not proceed" to replace FTA. IMPLICATIONS FOR NURSING MANAGEMENT: This article advocates for further consideration of collaborative models that engage the patient in their care journey and for consideration of the language used within the outpatient acute hospital setting, proposing the term 'appointment did not proceed.'
This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
Keywords: Ambulatory Care; Ambulatory Care Facilities; Appointments and Schedules; Chronic Disease; Continuity of Patient Care; Humans; Queensland; Reminder Systems